DISTRIBUTION OF ETHEREUM BLOCKCHAIN ADDRESSES - Seitenov, A.; Smagulova, G. (Scientific Journal of Astana IT University, 2020)
In the contemporary world, Ethereum is a very reliable financial saving among cryptocurrencies. It is also well known as a blockchain platform for creating and launching its own cryptocurrency. The applications run on Ethereum executed by a platform-specific cryptographic token, ether. During 2014, Ethereum had launched a pre-sale for ether, which had received an overwhelming response. Ether is used broadly for two purposes: it is traded as a digital currency exchange like other cryptocurrencies, and it is used inside Ethereum to run applications and even to monetize work. It should be noticed that the smart contract has brought a significant share of the success to Ethereum. The smart contract is a computer programme that independently performs assigned tasks between network participants without the participation of a third trusted party. Smart contracts and their intranet transactions have facilitated the rapid expansion of the Ethereum network. Smart contracts are widely represented on the market, either as electronic transaction payments or as applications for the implementation of logistics supplies, gambling, and other sectors. These transactions are irreversible and fully tracked online. Whereas the electronic records are available in a public distributed ledger and include data about user addresses, whereas the real names are hidden. The article explains the usage of decentralized accounts and their electronic transactions in the Ethereum network. The results are presented through different application sectors. Additionally, a new method for extracting blockchain records through node cluster via IPFS path is implemented in the research.